1998
DOI: 10.1116/1.581488
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of TiN films by N-implantation into evaporated Ti films

Abstract: Erratum: "Early nitriding stage of evaporated-Ti thin films by N-ion implantation" [J.Nitrogen ions (N 2 ϩ ) with 62 keV have been implanted into 100-nm-thick Ti films prepared by the evaporation on thermally cleaned NaCl substrates held at room temperature. The epitaxial growth process of resultant TiN films has been studied by transmission electron microscopy, Rutherford backscattering spectrometry, and elastic recoil detection analysis. It has been revealed that the ͑110͒-oriented TiN y is formed by nitridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…On the other hand, in the N-implanted Ti films with N/Ti<∼1.0, there coexist both hcp-Ti and TiN y crystallites. And the lattice expansions (strain) due to the occupation of N in the octahedral sites of hcp-Ti and fcc-Ti sublattice of TiN y in the present in-situ observation are observed, which is a reconfirmation of the lattice expansions reported in the ex-situ experiments [14]. Thus, the strain due to the increase in the lattice constant can be considered as one of the driving forces for the hcp-fcc transformation.…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…On the other hand, in the N-implanted Ti films with N/Ti<∼1.0, there coexist both hcp-Ti and TiN y crystallites. And the lattice expansions (strain) due to the occupation of N in the octahedral sites of hcp-Ti and fcc-Ti sublattice of TiN y in the present in-situ observation are observed, which is a reconfirmation of the lattice expansions reported in the ex-situ experiments [14]. Thus, the strain due to the increase in the lattice constant can be considered as one of the driving forces for the hcp-fcc transformation.…”
Section: Methodssupporting
confidence: 88%
“…Titanium films of 100 nm in thickness were deposited on thermally cleaned NaCl (001) surfaces held at RT and 250 • C, respectively, by an electron beam heating method in an ultra high vacuum. Detailed descriptions of the preparation method for deposited Ti films were presented in earlier papers [12][13][14]. The Ti films deposited at RT and 250 • C, separated from NaCl substrates, were respectively heated up to 350 • C at a heating rate of 2 • C/min in a 400 kV TEM combined with ion accelerators at JAEA-Takasaki [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reflections indicated by the four-index system and the three-index system with asterisks are obtained from the hcp-Ti and TiH x crystallites, respectively. The growth of both hcp-Ti and TiH x agrees with the results of previous papers [14][15][16]: Ti films deposited on NaCl substrates spontaneously absorbed hydrogen (H) atoms from the interior of the NaCl, and then Fig. 1(a), whereas the 00 · 2 and 01 · 1 reflections in Fig.…”
Section: A Deposited Ti Thin Filmssupporting
confidence: 80%
“…Recently, it was reported that NaCl-type (110)-and (001)-oriented TiN y crystallites were 'epitaxially' grown by the N-implantation into CaF 2 -type (110)-oriented TiH x and (03 · 5)-oriented hcp-Ti in the deposited Ti films held at room temperature (RT), respectively [14][15][16]; here, the term 'epitaxially' is used to denote the situation of partially inheriting the atomic arrangements of unimplanted TiH x and hcp-Ti. However, the detailed 'epitaxial' nitriding processes of Ti films with the domains of TiH x and hcp-Ti during N-implantation, as well as the epitaxial growth processes of (110)-oriented TiH x and (03 · 5)-oriented hcp-Ti in deposited Ti films, have not yet been sufficiently understood.…”
Section: Introductionmentioning
confidence: 99%